The "three M's" counter-measures to children's risky online behaviors: mentor, mitigate and monitor. (8th June 2021) - Renaud, Karen; Prior, Suzanne
Abstract : Purpose: The purpose of this paper is to scope the field of child-related online harms and to produce a resource pack to communicate all the different dimensions of this domain to teachers and carers. Design/methodology/approach: With children increasingly operating as independent agents online, their teachers and carers need to understand the risks of their new playground and the range of risk management strategies they can deploy. Carers and teachers play a prominent role in applying the three M's: mentoring the child, mitigating harms using a variety of technologies (where possible) and monitoring the child's online activities to ensure their cybersecurity and cybersafety. In this space, the core concepts of "cybersafety" and "cybersecurity" are substantively different and this should be acknowledged for the full range of counter-measures to be appreciated. Evidence of core concept conflation emerged, confirming the need for a resource pack to improve comprehension. A carefully crafted resource pack was developed to convey knowledge of risky behaviors for three age groups and mapped to the appropriate "three M's" to be used as counter-measures. Findings: The investigation revealed key concept conflation, and then identified a wide range of harms and countermeasures. The resource pack brings clarity to this domain for all stakeholders. Research limitations/implications: The number of people who were involved in the empirical investigation was limited to those living in Scotland and Nigeria, but it is unlikely that the situation is different elsewhere because the internet is global and children's risky behaviors are likely to be similar across the globe. Originality/value: Others have investigated this domain, but no one, to the authors' knowledge, has come up with the "Three M's" formulation and a visualization-based resource pack that can inform educators and carers in terms of actions they can take to address the harms.